Nitric oxide and nitrosative stress tolerance in yeast. (19th January 2011) - Tillmann, Anna; Gow, Neil A.R.; Brown, Alistair J.P.
Abstract : The opportunistic human fungal pathogen Candida albicans encounters diverse environmental stresses when it is in contact with its host. When colonizing and invading human tissues, C. albicans is exposed to ROS (reactive oxygen species) and RNIs (reactive nitrogen intermediates). ROS and RNIs are generated in the first line of host defence by phagocytic cells such as macrophages and neutrophils. In order to escape these host-induced oxidative and nitrosative stresses, C. albicans has developed various detoxification mechanisms. One such mechanism is the detoxification of NO (nitric oxide) to nitrate by the flavohaemoglobin enzyme CaYhb1. Members of the haemoglobin superfamily are highly conserved and are found in archaea, eukaryotes and bacteria. Flavohaemoglobins have a dioxygenase activity [NOD (NO dioxygenase domain)] and contain three domains: a globin domain, an FAD-binding domain and an NAD(P)-binding domain. In the present paper, we examine the nitrosative stress response in three fungal models: the pathogenic yeast C. albicans, the benign budding yeast Saccharomyces cerevisiae and the benign fission yeast Schizosaccharomyces pombe . We compare their enzymatic and non-enzymatic NO and RNI detoxification mechanisms and summarize fungal responses to nitrosative stress.